2011
DOI: 10.1074/jbc.m111.267294
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Truncated Eukaryotic Initiation Factor 3e (eIF3e) Resulting from Integration of Mouse Mammary Tumor Virus (MMTV) Causes a Shift from Cap-dependent to Cap-independent Translation

Abstract: Integration of mouse mammary tumor virus (MMTV) at the common integration site Int6 occurs in the gene encoding eIF3e, the p48 subunit of translation initiation factor eIF3. Integration is at any of several introns of the Eif3e gene and causes the expression of truncated Eif3e mRNAs. Ectopic expression of the truncated eIF3e protein resulting from integration at intron 5 (3e5) induces malignant transformation, but by an unknown mechanism. Because eIF3e makes up at least part of the binding site for eIF4G, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…In contrast, eIF3f is downregulated in melanoma and pancreatic cancer, and its overexpression inhibits proliferation and protein synthesis and induces apoptosis (33). The murine Int-6 gene, encoding eIF3e, was first identified as a mouse mammary tumor virus integration site (34,35) that results in the production of a truncated oncoprotein with transforming activity (36) capable of inducing cap-independent translation, as reported recently (37). Several subsequent studies of full-length eIF3e showed its tumor suppressor activity (38)(39)(40).…”
Section: Ires-mediated Translationmentioning
confidence: 92%
“…In contrast, eIF3f is downregulated in melanoma and pancreatic cancer, and its overexpression inhibits proliferation and protein synthesis and induces apoptosis (33). The murine Int-6 gene, encoding eIF3e, was first identified as a mouse mammary tumor virus integration site (34,35) that results in the production of a truncated oncoprotein with transforming activity (36) capable of inducing cap-independent translation, as reported recently (37). Several subsequent studies of full-length eIF3e showed its tumor suppressor activity (38)(39)(40).…”
Section: Ires-mediated Translationmentioning
confidence: 92%
“…PCR primers specific for XIAP isoforms, Bcl-x L , Apaf-1, VEGF-A, cIAP1, or GAPDH were used to amplify messages by the use of quantitative PCR as described above. Weighted averages (F W ) were calculated for the distribution of each mRNA as described previously (8). ⌬F W represents the difference between small interfering control cells and siPDCD4-treated cells in mRNA polysome distribution.…”
Section: Rna Extraction and Quantitative Rt-pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…HEK293T cells were initially transfected with PDCD4-targeting siRNA or a nonsilencing control siRNA. At 48 h later, the cells were transfected with the bicistronic reporter plasmids, and reporter protein levels were assayed after 24 h. We found that the activity of both the XIAP and Bcl-x L IRES elements was enhanced approximately (8). (E) Bicistronic DNA constructs containing XIAP or Bcl-x L IRES elements were transfected into HEK293T cells after treatment with PDCD4 siRNA or control (CTRL) siRNA.…”
Section: S6k2 Directly Interacts With and Phosphorylates Pdcd4mentioning
confidence: 99%
“…A recent study found that expression of a truncated eIF3e protein that lacks normal eIF3e activity (i.e., the ability to bind to eIF4G) causes both a decrease in global, cap-dependent translation initiation, and a concomitant increase in an alternative initiation mechanism that relies on RNA structures called internal ribosome entry sites (IRES; ref. 3), suggesting that decreased eIF3e activity creates an environment that is favorable for mRNAs that rely on capindependent translation. Some translation initiation factors have been shown to be involved in cancer development and progression (4), most notably the cap-binding protein eIF4E (5) whose overexpression has been correlated with many types of cancer (6), including breast (7,8) and lung (9) cancers.…”
Section: Introductionmentioning
confidence: 99%